Computational exploration of the dual role of the phytochemical fortunellin: Antiviral activities against SARS-CoV-2 and immunomodulatory abilities against the host. (October 2022) - Agrawal, Shivangi; Pathak, Ekta; Mishra, Rajeev; Mishra, Vibha; Parveen, Afifa; Mishra, Sunil Kumar; Byadgi, Parameswarappa S.; Dubey, Sushil Kumar; Chaudhary, Ashvanee Kumar; Singh, Vishwambhar; Chaurasia, Rameshwar Nath; Atri, Neelam
Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infections generate approximately one million virions per day, and the majority of available antivirals are ineffective against it due to the virus's inherent genetic mutability. This necessitates the investigation of concurrent inhibition of multiple SARS-CoV-2 targets. We show that fortunellin (acacetin 7-O-neohesperidoside), a phytochemical, is a promising candidate for preventing and treating coronavirus disease (COVID-19) by targeting multiple key viral target proteins. Fortunellin supports protective immunity while inhibiting pro-inflammatory cytokines and apoptosis pathways and protecting against tissue damage. Fortunellin is a phytochemical found in Gojihwadi kwath, an Indian traditional Ayurvedic formulation with an antiviral activity that is effective in COVID-19 patients. The mechanistic action of its antiviral activity, however, is unknown. The current study comprehensively evaluates the potential therapeutic mechanisms of fortunellin in preventing and treating COVID-19. We have used molecular docking, molecular dynamics simulations, free-energy calculations, host target mining of fortunellin, gene ontology enrichment, pathway analyses, and protein-protein interaction analysis. We discovered that fortunellin reliably binds to key targets that are necessary for viral replication, growth, invasion, and infectivity including Nucleocapsid (N-CTD) (−54.62 kcal/mol), Replicase-monomer at NSP-8 binding site (−34.48 kcal/mol), Replicase-dimer interface (−31.29 kcal/mol), Helicase (−30.02 kcal/mol), Papain-like-protease (−28.12 kcal/mol), 2′-O-methyltransferase (−23.17 kcal/mol), Main-protease (−21.63 kcal/mol), Replicase-monomer at dimer interface (−22.04 kcal/mol), RNA-dependent-RNA-polymerase (−19.98 kcal/mol), Nucleocapsid-NTD (−16.92 kcal/mol), and Endoribonuclease (−16.81 kcal/mol). Furthermore, we identify and evaluate the potential human targets of fortunellin and its effect on the SARS-CoV-2 infected tissues, including normal-human-bronchial-epithelium (NHBE) and lung cells and organoids such as pancreatic, colon, liver, and cornea using a network pharmacology approach. Thus, our findings indicate that fortunellin has a dual role; multi-target antiviral activities against SARS-CoV-2 and immunomodulatory capabilities against the host. Graphical abstract: Image 1 Highlights: Fortunellin has a dual role; multi-target antiviral against SARS-CoV-2, and immunomodulator against the host. Fortunellin targets the N-CTD, Replicase, Helicase, PLpro, 2′-O-methyltransferase, Mpro, RdRp, N-NTD and Endoribonuclease. Fortunellin targets TNF, IL6, ANPEP, CASP1, CD38, FGF2, FN1, MMP1, MMP7, PTGS2, and VEGFA of host proteins.